Odpowiedzi

2010-04-15T07:03:09+02:00
1)4x-3=3x+5 /-3x-3
x = 2

2)5x+2=7-3x /+3x-2
2x = 5 /:2
x = 2,5

3)3(x-1)=0
3x-3=0 /+3
3x = 3 /:3
x = 1

4)-6(x+1)=24
-6x-6=24 /+6
-6x=30 /:-6
x=-5

5)-7(x-2)=3x-1
-7x+14=3x-1 /+7x+1
15=10x /:10
1,5=x

6)4(x-1)=6(1+x)
4x-4=6+6x /-4x-6
-10=2x /:2
-5=x

7)0,2x+0,3=-0,5 /-0,3
0,2x=0,2 /:0,2
x=1

8)-1,5x-3=0,2x+6 /+1,5x-6
-9=1,7x /:1,7
2010-04-15T07:12:25+02:00
A)4x-3=3x+5 4x-3x=5+3 x=8
b)5x+2=7-3x 5x+3x=7-2 8x=5 x=5/8
c)3(x-1)=0 3x-3=0 3x=3 x=1
d)-6(x+1)=24 -6x-6=24 -6x=24+6 -6x=30 x=-5
e)-7(x-2)=3x-1 -7x+14=3x -7x-3x=-14 -10x=-14 x=10/14
f)4(x-1)=6(1+x) 4x-4=6+6x 4x-6x=6+4 -2x=10 x=-5
a)0,2x+0,3= -0,5 0,2x=-0,5-0,3 0,2x=-0,8 x=-4
b)0,4+0,25=-2 brak x?
c)2,1-0,3=0,4x 1,8=0,4x x=4,5
d)-1,5x-3=0,2x+6 -1,5x-0,2x=6+3 -1,7x=9 x=-5,27